1996
DOI: 10.1073/pnas.93.19.10417
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vascular endothelial genes differentially responsive to fluid mechanical stimuli: cyclooxygenase-2, manganese superoxide dismutase, and endothelial cell nitric oxide synthase are selectively up-regulated by steady laminar shear stress.

Abstract: Early atherosclerotic lesions develop in a topographical pattern that strongly suggests involvement of hemodynamic forces in their pathogenesis. We hypothesized that certain endothelial genes, which exhibit differential responsiveness to distinct fluid mechanical stimuli, may participate in the atherogenic process by modulating, on a local level within the arterial wall, the effects of systemic risk factors. A differential display strategy using cultured human endothelial cells has identified two genes, mangan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
499
6
19

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 778 publications
(563 citation statements)
references
References 49 publications
36
499
6
19
Order By: Relevance
“…It was not possible to use laminin 411 as the cells detached under even low flow conditions due to weak adhesion. Prostacyclin is released from endothelial cells under flow‐induced shear (Frangos et al , 1985) and its expression is controlled by COX2 (Topper et al , 1996); hence, elevated COX2 expression reflects an enhanced shear response. Figure 3B shows a higher fold change in COX2 mRNA and protein expression in shear versus non‐shear conditions in HUAECs plated on laminin 511 compared with laminin 111, consistent with a role for laminin 511 in shear‐induced arterial dilation in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…It was not possible to use laminin 411 as the cells detached under even low flow conditions due to weak adhesion. Prostacyclin is released from endothelial cells under flow‐induced shear (Frangos et al , 1985) and its expression is controlled by COX2 (Topper et al , 1996); hence, elevated COX2 expression reflects an enhanced shear response. Figure 3B shows a higher fold change in COX2 mRNA and protein expression in shear versus non‐shear conditions in HUAECs plated on laminin 511 compared with laminin 111, consistent with a role for laminin 511 in shear‐induced arterial dilation in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that this induction is cancer cell speciÂźc inasmuch as the endothelial cells, acinar and ductal cells, and Âźbroblasts also exhibited expression of Smad7 by in situ hybridization. Indeed, Smad7 was originally cloned from endothelial cells and the enhanced expression in this cell type is believed to promote endothelial cell proliferation (Topper et al, 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Smad2/Smad4 and Smad3/Smad4 complexes then translocate to the nucleus where they regulate gene transcription (Heldin et al, 1997;. Two novel members of the Smad family, Smad6 and Smad7, were cloned from vascular endothelial cells (Topper et al, 1996Hayashi et al, 1997;Imamura et al, 1997). They associate with the activated TbRI, thereby blocking access and phosphorylation of Smad2 (Hayashi et al, 1997;Imamura et al, 1997) and possibly Smad3.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have found that the presence of AA in human prostate cancer cells up-regulates COX-2 mRNA and protein expression [14,15] -specifically, the 72 kDa glycoform [16]. However, COX-2 is also involved with normal physiological processes such as neurotransmission and synaptic activity [17,18], maintaining normal renal functions [19], providing vascular protection [20], regulating cerebral blood flow [21], and facilitating pregnancy [22].…”
Section: Introductionmentioning
confidence: 99%